2016
DOI: 10.1111/ecog.02578
|View full text |Cite
|
Sign up to set email alerts
|

Colour lightness of dragonfly assemblages across North America and Europe

Abstract: Dark‐coloured ectotherms absorb energy from the environment at higher rates than light‐coloured ectotherms. The thermal melanism hypothesis (TMH) states that this physical mechanism links the colour lightness of the body surfaces of ectotherms to their thermal environment and hence to their geographical distribution. Studies on different insect taxa in Europe found support for this prediction of the TMH. However, whether these results hold also for other biogeographical regions remains unclear. Here, we quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 53 publications
14
84
0
1
Order By: Relevance
“…These declines in colour lightness with latitude and elevation are reflected in the overall geographical pattern of geometrids of the Western Palearctic. Strikingly, this geographical variation in colour lightness strongly resembles the outlined pattern expected if only thermoregulatory functions of dark or light coloration were of importance, as has been discussed with regard to heliophilic insects, such as butterflies and dragonflies (Pinkert et al, ; Zeuss et al, ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These declines in colour lightness with latitude and elevation are reflected in the overall geographical pattern of geometrids of the Western Palearctic. Strikingly, this geographical variation in colour lightness strongly resembles the outlined pattern expected if only thermoregulatory functions of dark or light coloration were of importance, as has been discussed with regard to heliophilic insects, such as butterflies and dragonflies (Pinkert et al, ; Zeuss et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…Recent studies revealed contrasting geographical patterns in the colour lightness of insects, the majority of which are ectothermic. Among insects, darker‐coloured species occur at high latitudes, presumably because of the thermoregulatory advantages of dark coloration (Bishop et al, ; Pinkert, Brandl, & Zeuss, ; Schweiger & Beierkuhnlein, ; Zeuss, Brandl, Brändle, Rahbek, & Brunzel, ). Hence, whether dark or light coloration is favoured in a particular environment might depend on different selection pressures that operate simultaneously and are not mutually exclusive but vary in their relative importance depending on the physiology and behaviour of animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ants are natural enemies of caterpillars, but not for healthy adult butterflies (Shapiro, 1974;Floren et al, 2002). Light-coloured butterfly assemblages primarily found in hot open habitats are therefore likely to be attributable to thermoregulation purposes other than predation avoidance (Pinkert et al, 2016;Xing et al, 2016). However, in open habitats, only D. leucophaeus and C. emma were regularly observed (W. Cheng, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, across Western Europe, dark‐coloured insect species are more prevalent in cooler climates (Zeuss et al., ). Pinkert, Brandl, and Zeuss () uncovered comparable patterns of colour lightness in dragonfly assemblages in North America, even though the geographical settings and biogeographical history are likely to be different between these two continents. Finally, in Asia, Xing et al.…”
Section: Introductionmentioning
confidence: 99%